Development of a Low-Cost TiO2/CuO/Cu Solar Cell by using Combined Spraying and Electroplating Method - Mamat Rokhmat; Edi Wibowo; Sutisna Sutisna; Khairurrijal Khairurrijal; Mikrajuddin Abdullah (Institute for Research and Community Services (LPPM) ITB, 2018)
A simple method is proposed to develop a low-cost TiO2/CuO/Cu based solar cell. The cell is made by employing a lower grade (technical grade) of TiO2 as the active material. CuO powder is synthesized using a wet chemical method and mixed with TiO2 powder to give impurity to the TiO2. A layer of TiO2/CuO is then deposited onto fluorin-doped tin oxide (FTO) by spraying. Copper particles are grown on the spaces between the TiO2 and/or CuO particles by electroplating for more feasible electron migration. The TiO2/CuO/Cu solar cell is finalized by sandwiching a polymer electrolyte between the film and the counter electrode. Current-voltage measurement was performed for various parameters, such as the molarity of NaOH for producing CuO particles, the weight ratio of CuO over TiO2, and the current in the electroplating process. A highest efficiency of 1.40% and a fill factor of 0.37 were achieved by using this combined spray and electroplating method.